PELAYANAN INSTALASI FARMASI POLI RAWAT JALAN TERHADAP INDEKS KEPUASAN PASIEN KLINIK RAWAT INAP UTAMA PEMUDA BOJONEGORO - jurnalmap map; Yuli Setiyanto; Hadi Susanto; Arini Sulistyowati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
The purpose of this study is to describe the level of community satisfaction as a service user based on the Ministry of Education and Culture No. 14 of 2017. Nine elements that are used as indicators of measuring community satisfaction with public service providers are requirements, systems, mechanisms and procedures, completion time, fees / rates, Product specifications for types of services, Competence of implementers, Behavior of implementers, Handling of complaints, Suggestions and input, Services and Infrastructure. This study uses a descriptive method with a quantitative approach, the study population is outpatient poly patients who redeem prescription drugs and meet the sampling criteria in the Pharmacy Installation, sampling techniques using non-probability sampling methods by means of purposive sampling where the determination of the sample with special consideration so that it is suitable to be made sample. Calculation of the Community Satisfaction Index of service units in the Bojonegoro Youth Main Inpatient Clinic obtained a value of 74.49 that falls into the category of service quality C and the performance of the service unit falls into the unsatisfied category.Keywords: health services, community satisfaction index.